Pharmacokinetics, tissue levels and dosage regimen of cefazolin in dogs with urethral obstruction - HARIKA, J S; SAINI, N S; SRIVASTAVA, A K; ANAND, A (The Indian Journal of Animal Sciences, 2014)
Dogs (10) were divided into 2 groups of 5 animals each, In animals of group I uretroromy and cystotomy wac perfomedwithout creatingany urinary obstruction whereas in dogs of group 2 urethral ligation, for 36 hr. at pre-scrotal site behind the os-penis was done and then uretrolomy and cystomy were performed. In dogs of both the groups. cefazolin was administered intravenously @ 10 mg kg-1 body weight. In both the groups cefazolin followed 2 compartment open model and first order kinetics. The peak plasma concentration of cefazolin at 2 min was 46.81±0.44 and 55,33±0.50 ug/ml in group 1 and 2, respectively, whereas, at 7 hr the respective concentrations were 0.44±0.06 and 1.43±0,04)ug ml-1 The 1β were 2.6±0.003 and 1 83±0.001 hr in animals of groups 1 and 2 were 5.52±0.29 and 1.66±0, 10 respectlively. Total body clearance (clB) were 454, 16±7,57 and 154.42±1.78 L kg-1hr-1 in groups 1 and 2 respectively. In both groups of animals the urine concentration of cefalolin remained well above its MIC throughout tne study. The ccfwolin concentration at 1hr after single intravenous dose were 37.98±0.70 and 11.58±0.95 in the urinary bladder tissue in group 1 and 2 respectively. The optimum dosage regimen calculated on the basis of results of kinetic data in groups 1 and 2 was 10 mg kg-1 to be repeated at 12 hr intervals.